O silêncio e o audiovisual: complexidades dos processos de criação sonora - Alexandre, Fernanda Galetti (2024)
In the context of the field of communication, and within the line of research on creative processes in communication and culture, this master's thesis aims to contribute to the understanding of the complexities of the role of silence in audiovisual sound design. The dissertation begins by presenting a mapping of the meanings of silence in culture, film theories, arts, and literature, and dialogues with the thoughts of Chion, Cage, Murch, among others. To deepen the understanding of the complexities of silence in cinematographic language, we conducted an exercise in selection, editing, and curatorship in the format of a video essay. The experimentation, developed using Leão's method of cartography of imaginaries, allowed us to unveil different types of silence in cinema, and as a result, we proposed a typology. We then undertook a case study of a film, focusing on sound design and the importance of silence. Finally, we organized a series of notes on the teaching of sound creation processes and the uses of silence in cinema, aiming to establish bridges between theories, critical analysis, audiovisual production, and the expansion of perception and knowledge on the subject. Among the results achieved in the research, we list: a revision of the concept of silence in culture and imagination; curating uses of silence in cinema; a typology of dominances of silence in the audiovisual; and the proposition of principles for thinking about the teaching of sound design and practical applications of silence